Madagascar : Rural and Environmental Sector Review, Volume 2. Technical Annexes - World Bank (Washington, DC, 2013)
This review aims to provide the Government of Madagascar with a situation assessment and insights and guidance on how to position the rural and environment sector as an engine for inclusive and sustainable economic growth. The review has cast the analytical net quite widely with the aim to come up with a comprehensive overview of the sector. In view of the intimate linkages between rural development and the environment, which are particularly important because of Madagascar's unique biodiversity, the review looks into both the production and conservation aspects of natural resources management for inclusive and sustainable economic growth. The report is divided into two Volumes. Volume 1, the Main Report, is aimed at policy makers and particularly focuses on the recommendations that flow from the analytical work that has been conducted as part of the review. It is organized along four axes that represent the strategic challenges faced by the rural and environment sector to establish itself as an engine of inclusive and sustainable economic growth in Madagascar: (i) improve food security and food production; (ii) put in place the building blocks for sustainable intensification and diversification of agricultural production; (iii) improve value-added of natural resources as providers of extractive products and environmental services; and (iv) make the sector institutional framework more effective and efficient. A brief diagnostic overview of the sector precedes the presentation of these axes. Volume 2, Technical Annexes, is aimed at sector experts and rural development practitioners and provides the underlying analytical groundwork for the recommendations that are presented in the Main Report. For this purpose, Volume 2 includes a detailed situation assessment of the sector.